2015
DOI: 10.1007/s10071-015-0938-1
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic numerical discrimination in mice

Abstract: Previous studies showed that both human and non-human animals can discriminate between different quantities (i.e., time intervals, numerosities) with a limited level of precision due to their endogenous/representational uncertainty. In addition, other studies have shown that subjects can modulate their temporal categorization responses adaptively by incorporating information gathered regarding probabilistic contingencies into their time-based decisions. Despite the psychophysical similarities between the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…First, and most importantly, all but one of our subjects based their decision at least in part on counting—in support of the original intention of the task (Mechner, 1958a,b), as well as decades of previous work manipulating the task (Mechner and Guevrekian, 1962; Wilkie et al, 1979; Machado and Rodrigues, 2007; Fetterman and Killeen, 2010) and analyzing data from similar tasks (Berkay et al, 2016; Çavdaroğlu and Balcı, 2016). Most mice, regardless of count requirement and which time (trial or run) the count strategy was compared to, demonstrated a count-based contribution to the decision to switch levers.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…First, and most importantly, all but one of our subjects based their decision at least in part on counting—in support of the original intention of the task (Mechner, 1958a,b), as well as decades of previous work manipulating the task (Mechner and Guevrekian, 1962; Wilkie et al, 1979; Machado and Rodrigues, 2007; Fetterman and Killeen, 2010) and analyzing data from similar tasks (Berkay et al, 2016; Çavdaroğlu and Balcı, 2016). Most mice, regardless of count requirement and which time (trial or run) the count strategy was compared to, demonstrated a count-based contribution to the decision to switch levers.…”
Section: Discussionsupporting
confidence: 54%
“…Roberts et al (2000) then demonstrated that these attributes can be brought under stimulus control with a discriminatory cue presented prior. Recently, Berkay et al (2016) investigated animals’ strategies by modeling performance in a numerical switch task. This task, similar to the one employed by Fetterman and Killeen (2010), allowed the group to investigate the influence of when the animals’ chose to move from the “few” response lever to the “many” response lever.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time it was believed that non-symbolic numerical comprehension could occur solely after intensive numerical training and if (and only if ) any other continuous extent could guide animal behaviour [26]. In recent decades, it has been demonstrated that purely numerical skills (when the possible use of continuous extents was prevented) are widespread within the animal kingdom [17,[67][68][69]. Nevertheless, studies proving early numerical abilities in non-human animals were sparse.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, animals can encode a number even when other, non-numerical cues are also available. This means that number processing is not employed as a last-resort strategy-for example, only when the non-numerical cues are unavailable (Berkay et al 2016;Kawai and Matsuzawa 2000;Biro and Matsuzawa 2001;Benson-Amram et al 2011;). In the natural environment, though, usually numerical cues co-vary with other continuous information.…”
Section: Discussionmentioning
confidence: 99%